The study of maternal outcome of early onset severe pre eclampsia with expectant management - Viswanathan, Manjusha; Daniel, Suja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Hypertensive disorders in pregnancy forms one of the deadly triads along with hemorrhage and jaundice which result in maternal death. The present management is termination of pregnancy which causes high neonatal morbidity. Hence the study is done to assess the outcome of prolongation of pregnancy. The aim of this study was to evaluate the safety and outcome of women undergoing expectant management of early onset severe pre eclampsia. Methods: Prospective case series extending over 1 year in a tertiary care teaching hospital. All women with singleton pregnancy presenting with severe pre eclampsia with gestational age (GA) less than 34 weeks were included in the study. All patients with major maternal or fetal complications were excluded. The included patients were admitted in the intensive care labor ward for non-invasive monitoring of mother. The patients were treated with anti hypertensives, β methasone injection and prophylactic magnesium sulphate when required. They were monitored with regular 4 hrly BP charting, lab investigations and fetal monitoring. The data obtained were expressed as means with standard deviation and median with range. The difference in mean were analysed, the chi-square test was applied to quantitative variables. Results: In women recruited in the study after expectant management the mean and median number of days gained by women ante partum was 16.7 and 14.2 days respectively. It is seen that most of the complications occurs after 30 weeks of gestation. There was no death reported. Conclusions: The results of the study showed that it was best to put the women presenting with early onset severe pre eclampsia in expectant management and deliver her after 34 weeks. This was achieved with no increased mortality or morbidity to mother.